2017
DOI: 10.1097/mph.0000000000000784
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity Associated With Dimethyl Sulfoxide Used in Allogeneic Stem Cell Transplantation

Abstract: Dimethyl sulfoxide (DMSO) is a cryoprotective agent used in storage of frozen stem cells in stem cell transplantation. Central nervous system side effects of DMSO such as epileptic seizures, stroke, transient global amnesia, and temporary leucoencephalopathy are rarely seen. Here, we report a pediatric patient who developed seizures after DMSO-cryopreserved stem cell infusion and whose magnetic resonance imaging of the brain demonstrated parietal and occipital focal cortical T2-signal intensity increase. DMSO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…That confirms the toxicity of this cryoprotective agent to ASCs, being a toxic substance at room temperature that damages cells when used at high concentrations or inadequately. Other researchers have reported that cryopreservating cells using DMSO at 10 % concentration within the medium has caused adverse effects in patients that receive stem cells as therapy, such as: respiratory reactions and neurotoxicity in pediatric patients, which clearly indicates the need to reduce its use or look for other cryoprotective agents when aiming to scale up to clinical therapies [37] [38].…”
Section: Discussionmentioning
confidence: 99%
“…That confirms the toxicity of this cryoprotective agent to ASCs, being a toxic substance at room temperature that damages cells when used at high concentrations or inadequately. Other researchers have reported that cryopreservating cells using DMSO at 10 % concentration within the medium has caused adverse effects in patients that receive stem cells as therapy, such as: respiratory reactions and neurotoxicity in pediatric patients, which clearly indicates the need to reduce its use or look for other cryoprotective agents when aiming to scale up to clinical therapies [37] [38].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 18 studies that composed the sample, two were of the case report type and 16 used other methodologies. The frequency of adverse reactions varied from 0% with the infusion of fresh bone marrow (33) to 80% with the infusion of umbilical cord blood and cryopreserved placental blood (22) . A study developed in Canada with pediatric patients receiving fresh BM showed a 45% frequency of AR that are related to the final volume of the product and the presence of incompatibility of the ABO system between donor and recipient (2,14) .…”
Section: Discussionmentioning
confidence: 99%
“…In 13 studies, the source of the HSC was peripheral blood (5,12,(18)(19)21,(23)(24)(25)(26)(27)(28)(29)32) . A Turkish study used only bone marrow (33 ) and another Japanese study only the umbilical cord and the placental blood (22) . Only in the Italian and Canadian studies more than one source were used: BMandPB (20) and the three sources (31) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations